Creative Product Learning Model and Entrepreneurship through the Company Establishment Program - Kasmi Kasmi; Didik Nurhadi; Nunung Nurjanah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Vocational high schools are formal institutions that can demonstrate skills in certain fields. Vocational high school entrepreneurship should be able to stand out along with the number of unemployed. Learning related to entrepreneurship can be used by vocational high schools as a provision for the future for students. The efforts of vocational high schools in providing learning for independent and productive readiness are by doing the practice of establishing a company that is packaged in creative product learning and entrepreneurship (PKK). The research method used is descriptive research with a qualitative approach. Data collection techniques in this study used the methods of observation, interviews, and documentation. Sources of data in the study was the head of the study program, PKK teachers, and students. The results of the analysis and discussion of the research obtained, it can be concluded, among others: (1) student learning planning which begins with a teacher coordination meeting with the head of the expertise program, administrative preparation for the preparation of lesson plans from the syllabus and analysis of talents and interests. After conducting meetings and administrative preparations, then proceed with technical preparations, namely conducting cooperation marked by MoUs with productive business actors, which in the future will conduct workshops, seminars, financial support, and student psychology; (2) the implementation of student learning in fostering an entrepreneurial spirit and financial intelligence, namely PKK learning in which there is the development of entrepreneurial knowledge, developing student potential, giving projects, practical experience in entrepreneurship and financial management, taking advantage of opportunities, reading market trends, and monitoring evaluations; (3) there are several obstacles, namely teachers do not have entrepreneurial experience in the field. In addition, the obstacles are also felt by students who have not been able and satisfied in selling the products they sell. As an effort to solve problems by providing direct assistance and discussing with practitioners of productive business actors.